ARID2, a Rare Cause of Coffin–Siris Syndrome: A Clinical Description of Two Cases - Wang, Xiaoyan; Wu, Haiying; Sun, Hui; Wang, Lili; Chen, Linqi (Frontiers in Pediatrics, 2022)
Abstract Background Coffin-Siris syndrome (CSS) is a multiple congenital anomaly syndrome characterized by coarse facial features, sparse scalp hair, hypertrichosis, and hypo/aplastic digital nails and phalanges. Mutations in the BAF (SWI/SNF)-complex subunits (SMARCE1, SMARCB1, SMARCA4, SMARCA2, ARID1B, and ARID1A) have been shown to cause CSS. Although more and more people are diagnosed with BAF pathway diseases, ARID2 is the least common of these genes. However, only 16 individuals with CSS have been reported to have pathogenic variants in ARID2. Case presentation In this article, we introduced two individuals with clinical features consistent with CSS6. This article increases the number of patients with these mutations, provides better phenotypic information for this rare syndrome, and allows everyone to better understand the disease. Conclusion Our observations indicate that ARID2 mutations could have variable phenotypes, even in patients from the same family.